PREVALENCE COMPARISON OF NEWCASTLE DISEASE VIRUS CASES AT CHICKEN FARMS IN BLAHBATUH AND PAYANGAN SUBDISTRICTS, GIANYAR DISTRICT - Ingrid Laurentina; Gusti Ayu Yuniati Kencana; I Made Kardena (Buletin Veteriner Udayana, 2025)
Newcastle Disease (ND) is a common poultry disease in Indonesia, caused by Avian Paramyxovirus serotype 1 (APMV-1). This disease is endemic and occurs throughout the year affecting various types of poultry, including commercial and backyard chickens. This study aims to compare the prevalence of the ND virus in poultry farms in Blahbatuh and Payangan Districts, Gianyar Regency. This study employed an observational method with a cross-sectional approach. Chickens showing clinical symptoms were subjected to necropsy to collect tissue samples that exhibited pathological changes. These samples were inoculated into Specific Pathogen-Free (SPF) embryonated chicken eggs for ND virus growth. After incubation, the allantoic fluid was harvested and tested using HA and HI. A positive HA test result was indicated by the formation of sand like sediment, while a positive HI test result showed a 1% erythrocyte deposit forming a dot at the bottom of the microplate well. The study results indicated that 9 out of 32 chickens (28%) tested positive for ND. Chickens sampled in Payangan Subdistrict were found to have a 1.36 times higher risk of infection compared to those sampled in Blahbatuh subdistrict. Increasing farmers awareness of the importance of regular ND vaccination and improving biosecurity like isolation cage systems is crucial to preventing the spread of the disease.